Теория прочности и критерии разрушения: учебное пособие - Соколова Е. К. Евгения Кузьминична; Хорешок А. А. Алексей Алексеевич; Герике Б. Л. Борис Людвигович; Герике П. Б. Павел Борисович; Аксёнов В. В. Владимир Валерьевич (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана